Developing weblog design in Indonesian creative writing material - Siti Ansoriyah (Universitas Muhammadiyah Malang, 2021)
The sentences spoken by the actors in the dialogue contained in the film “the Professor and the Madman” consist of a variety of structures that form a grammatical construction, so that the sentences can be understood and the dialogue can run well and smoothly. In the context of Charles J. Fillmore’s case grammar, the various structures that form a grammatical construction in a sentence are called modality and proposition. In a line with that background, the purposes of the research are: (1) to reveal the modality in film “the Professor and the Madman” based on the perspective of Charles J. Fillmore; (2) to describe the proposition in film “the Professor and the Madman” based on the perspective of Charles J. Fillmore. This research is qualitative, descriptive and literary research. The data source in this research is film “the Professor and the Madman” directed by P.B. Shemran. The data collection techniques in this research use watching, reading-listening and taking note. The data analysis techniques consist of three stages, namely: (1) choosing and classifying data based on modality and its forms; and proposition and its forms; (2) illustrating and writing down case grammar elements and their forms on the table, explaining them sequentially and interpreting them based on Charles J. Fillmore’s perspective; and (3) conducting the induction of interpretation summary to obtain substantive and formative conclusions. The results are: (1) modality has types, including tense: past, present and future; mode: desiderative, imperative, indicative, and interrogative; negation: no and not; adverb: frequency, manner, degree, quantity, and explanatory; (2) there are several types of proposition. They are agentive case (A): first personal pronoun, second pronoun, and third pronoun; experiential case (E): verb (basic) and verb (modal); instrumental case (I): noun and sense; objective case (O): human and thing; source case (S): noun phrase and noun; goal case (G): human and place; locative case (L): area, part of house, and office; time case (T): part of the day, year, and century; collateral case (C): with + noun; and benefactive case: for + noun. Based on the results of this research, it can be concluded that if a sentence is viewed from the case grammar theory, then it must have an inner structure consisting of modality and or proposition. Modality and proposition consist of types and each of types has the various forms.